A SNAPSHOT OF INDONESIAN VOCATIONAL EDUCATION AND THE 21ST CENTURY SKILLS CHALLENGE - Loso Judijanto; Hasdiana; Ulin Naini; Al-Amin (CV. ADIBA AISHA AMIRA, 2024)
Vocational education in Indonesia faces various challenges in preparing competent and adaptive human resources for the 21st century. Despite various initiatives to improve the quality and relevance of vocational education, educational institutions still struggle with a less dynamic curriculum, limited infrastructure, and lack of collaboration with industry. As a result, vocational education graduates are often unprepared for the fast-changing and highly-skilled world of work. This challenge calls for a comprehensive reform of the vocational education system, involving the integration of 21st century skills such as adaptability, collaboration, critical thinking and digital literacy into the curriculum. It is also necessary to encourage strong partnerships between educational institutions and the industrial world to create a curriculum that is relevant and in line with labour market needs. In addition, the application of modern technology in the learning process, comprehensive training for teaching staff, and the development of high-quality vocational centres need to be prioritised. With consistent and coordinated reforms, vocational education in Indonesia is expected to be able to act as the main pillar in supporting the availability of competent and qualified human resources, and be able to compete at the global level. This will require close collaboration between government, industry and educational institutions to address the 21st century skills challenges and contribute to the nation's economic and social development.